Destination Landscape Attributes Influencing Tourists’ Perceptions of Image: Evidence from a Coastal Destination - Zeynali, Elmira (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
It is clear that there is a connection with building design and tourism in this study wants to figure out an important role of united making design landscape attributes in Famagusta (Northern Cyprus) as an example. Moreover, this research wants to survey the effect of these attributes on travelers' in terms of satisfaction and intention to return, and also, the aim of this thesis is to test the direct impact of destination landscape attributes on visitor's, tourist’s quality of experience or memorability, trip satisfaction and intention to return. This survey used the paper base and the total responses were 163 collected. The quantitative study method making SPSS has used to examine the thesis hypothesis. Outcomes display the different destination landscape attributes that have an effect on the Cyprus travelers in terms of quality of experience both positively and negatively. The tourist's quality of the experience played an important role in first of visitors' trip satisfaction and also the mediator in destination landscape attributes and intention to return which study shows that the flow of making Cyprus visitors' aims of small coastal towns carrying with their conception from destination landscape attributes, the quality of experience or memorability, and also trip satisfaction in considering. According to the outcome, both theoretical and practical implications, limitations, and suggestions for future study are considered.

ÖZ: Bu çalışmada bina tasarımı ve turizm ile bir bağlantı olduğu açıktır, bu örnekte Mağusa'da (Kuzey Kıbrıs) birleşik tasarım peyzajı niteliklerinin önemli bir rolünün ortaya çıktığı görülmektedir. Dahası, bu araştırma bu özelliklerin gezginlerin memnuniyet ve geri dönüş niyeti üzerindeki etkisini araştırmak istiyor ve ayrıca bu tezin amacı, hedef peyzaj özelliklerinin ziyaretçinin, turistin deneyim kalitesi veya hatırlanabilirlik, gezi memnuniyeti ve geri dönüş niyeti. Bu ankette kağıt tabanı kullanılmış ve toplam yanıtlar 163 olarak toplanmıştır. SPSS yapımında kullanılan nicel araştırma yöntemi tez hipotezini incelemek için kullanılmıştır. Sonuçlar, Kıbrıslı gezginler üzerinde hem olumlu hem de olumsuz deneyim kalitesi açısından farklı hedef peyzaj özelliklerini göstermektedir. Turistin deneyim kalitesi, ziyaretçilerin gezi memnuniyetinde ilk olarak önemli bir rol oynamıştır ve aynı zamanda hedef peyzaj özellikleri ve geri dönme niyetinde arabulucu, bu çalışma, Kıbrıs ziyaretçilerinin anlayışlarını taşıyan küçük sahil kasabalarının amaçlarını yapma akışının hedef peyzaj özellikleri, deneyim kalitesi veya hatırlanabilirlik, ve aynı zamanda dikkate dikkate memnuniyet. Sonuca göre, gelecekteki çalışma için hem teorik hem de pratik çıkarımlar, sınırlamalar ve öneriler dikkate alınmaktadır.
Master of Science in Tourism Management. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Tourism, 2020. Supervisor: Prof. Dr. Habib Alipour
Keywords: Tourism Faculty; Tourism Management; Islands tourism, Cyprus traveler, Destination attributes, Tourists experience quality or memorability, Trip satisfaction, Intention to revisit